Kedudukan Norma Hukum dan Agama Dalam Suatu Tata Masyarakat Pancasila - Arif Wijaya (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
in Indonesian society post-New Order era social conflicts broke out in several regions. Such conflicts originate from the issue of SARA (ethnicity, religion, race, group) with religion-based conflicts being dominant. As a result, there is a strong reservation about the success of Pancasila as national ideology in inspiring national unity and social integration.    Such perception may lead to a belief that Pancasila indeed is the culprit of that failure. It means that Pancasila is no longer viewed compatible with the demands of social integration and national resilience. Therefore, it is a mounting task for Indonesian citizens to revive peaceful, tolerant religious lives as a civilized society.  Many levels of Indonesian community do not understand that Pancasila contain values. It means that Pancasila is not only to organize national and social interaction, but also the values of Pancasila should be the inspiration for norms upheld by community. It is this aspect that needs correction; values should be materialized in form of norms. In reality, the norms maintained by community are not consistent with Pancasila values. Such values were translated into particular norms which serve particular interests which in turn make many people inappropriately attribute such misperception to Pancasila. to fix this problem, one must understand the position of religious and legal norms within the context of Pancasila. Religion should be in the central point in the implementation of Pancasila. That Pancasila is national philosophy, vision and the sole basis for political parties and social organizations, therefore all aspect of political and legal activities should be based on and aimed at Pancasila. If this principle is understood and executed, Indonesian citizens will eventually protect the existence of Pancasila as national heritage from the founding fathers.